THE RELATIONSHIP BETWEEN SMOKER TYPES AND HYPERTENSION LEVELS IN TAMANHARJO VILLAGE SINGOSARI SUB-DISTRICT, MALANG REGENCY - Erista, Evi Arum; Subekti, Imam; Sulastyawati, Sulastyawati; Marsaid, Marsaid (Indonesian Journal of Applied Health, 2025)
Smoking is a common activity in daily life in society. Hypertension is one of the most common cardiovascular system diseases, followed by coronary heart disease, and several other cardiovascular disorders. The purpose of this study was to determine the relationship between smoker types and hypertension levels in Kebonagung Hamlet, Tamanharjo Village, Singosari. This type of research is analytic observational with a cross-sectional research design, with a population of 65 people and a sample of 65 people. The sampling technique used was nonprobability sampling, namely the purposive sampling method. Researchers used data collection methods with unstructured free interviews and observation. Bivariate analysis in this study was carried out using the Chi-square test. The results of this study show: 1. There were 33 smokers as active smokers and 32 people as passive smokers with the highest frequency at the age of 56-65. 2. Among active smokers who experienced mild hypertension were 36.4%, moderate hypertension was 42.4%, and severe hypertension was 21.2%. Meanwhile, for passive smokers who experienced mild hypertension were 46.9%, moderate hypertension was 25%, and there was no severe hypertension 28.1%. 3. The results of the bivariate analysis of the Chi-Square Test showed a p-value sig (2 sided) of 0.332 > ? 0.05, indicating that there is no relationship between smoker type and hypertension level in Kebonagung Hamlet, Tamanharjo Village, Singosari.